2016
DOI: 10.1080/10926755.2016.1217574
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Identity Experiences Among Adult Transnational Adoptees: A Qualitative Study

Abstract: To establish more comprehensive ways to assess transnational adoption adjustment, we need to better understand the adoptive identity experiences of transnational adoptees. We explored adoption identity by describing sociopsychosocial aspects and self experiences related to transnational adoption adjustment in a purposive sample of 16 adult Korean-American adoptees. A qualitative, descriptive analysis resulted in three themes: biological parents, birthdays, and adoption history, with three subthemes of adoptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…The findings in our systematic review reflects that the field of adoption is relatively young with limited research in other areas of adoption as well (e.g., clinical work with adult adoptees). There are, for example, few validated assessment tools for measuring attachment in adopted children, especially in older children (Kerr & Cossar, 2014), and, based on adult adoptees experiences, there is a need to address issues such as their acceptance of adoption or adoption identify, for which there are few, if any, tools for clinicians to work with (Darnell, Johansen, Tavakoli, & Brugnone, 2017). Many adoption studies have thus far focused more on basic research such as adoptees' and adoptive parents' adjustment to adoption or their physical or mental health (see e.g., Askeland, Hysing, Aarø, Tell, & Sivertsen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The findings in our systematic review reflects that the field of adoption is relatively young with limited research in other areas of adoption as well (e.g., clinical work with adult adoptees). There are, for example, few validated assessment tools for measuring attachment in adopted children, especially in older children (Kerr & Cossar, 2014), and, based on adult adoptees experiences, there is a need to address issues such as their acceptance of adoption or adoption identify, for which there are few, if any, tools for clinicians to work with (Darnell, Johansen, Tavakoli, & Brugnone, 2017). Many adoption studies have thus far focused more on basic research such as adoptees' and adoptive parents' adjustment to adoption or their physical or mental health (see e.g., Askeland, Hysing, Aarø, Tell, & Sivertsen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, advice to adoptive parents has encouraged them to tell adoptees that they are 'chosen' and consequently 'special' (Raymond, 1955). In their qualitative research, Darnell et al (2017) found many of the adults they interviewed identified as 'chosen'. For some, this came with a sense of pride at being adopted which helped to mitigate some of the 'stigmas'.…”
Section: The Adoption Experience and Potential Implicationsmentioning
confidence: 99%
“…They may be unaware that they are at high-risk for a condition and eligible for disease prevention interventions limiting healthcare providers’ abilities to appropriately manage these patients’ disease risks 4 5. Adoptees are a unique population in which their group identity is defined by their adopted status 6. Group identity, which is determined by group memberships, contributes to an individual’s social identity, or sense of self 7.…”
Section: Introductionmentioning
confidence: 99%